Collective Expression of Persipa Pati Football Supporters Fanaticm Through the “Diurus Cah-Cah” Movement - Mareno Andrian Winanda; Mugiyo Hartono (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This study examines the collective expression of fanaticism of Persipa Pati supporters through the "Diurus Cah-Cah" movement. Research problems include how forms of collective fanaticism are formed, the driving factors for the emergence of movements, and their impact on the sustainability of the club. This study aims to analyze forms of collective expression, identify causative factors, and assess their impact. The approach used was qualitative descriptive with a purposive sampling technique of 15 informants consisting of supporters, management, fans, and the community. Data was collected through interviews, observations, and documentation, and tested by triangulation. Data analysis was carried out through the stages of reduction, presentation, and drawing conclusions. The results of the study show that collective fanaticism is formed through three main aspects, namely social solidarity, dynamics of collective consciousness, and social integrity and stability. Solidarity is seen through shared activities such as chant, choreography, and social activities. This movement is driven by a sense of belonging, disillusionment with management, and the collective identity of supporters. In addition, this movement has a positive impact by increasing supporter involvement, harmonious relationship with management, and contributing to team performance. It can be concluded that supporters' fanaticism is not only emotional, but also a constructive collective force in supporting the sustainability and development of football clubs.